Prevalence, risk factors, and predictors of female sexual dysfunction in a primary care setting: A survey finding - Ishak, I.H.; Low, Wah-Yun; Othman, S. (Wiley-Blackwell, 2010)
Introduction. Female sexual dysfunction (FSD) is a highly prevalent sexual health problem but poorly investigated at the primary care level. Aim. This article examines the prevalence of sexual dysfunction and its possible risk factors associated with women at high risk of FSD in a hospital-based primary practice. Methods. A validated Malay version of the Female Sexual Function Index (MVFSFI) was utilized to determine FSD in a cross-sectional study design, involving 163 married women, aged 18-65 years, in a tertiary hospital-based primary care clinic in Kuala Lumpur, Malaysia. Sociodemographic, marital profile, health, and lifestyle for women at high risk of FSD and those who were not at high risk were compared and their risk factors were determined. Main Outcome Measures. Prevalence of FSD in Malaysian women based on the MVFSFI, and its risk factors for developing FSD. Results. Some 42 (25.8%) out of 163 women had sexual dysfunction. Prevalence of sexual dysfunction increased significantly with age. Sexual dysfunctions were detected as desire problem (39.3%), arousal problem (25.8%), lubrication problem (21.5%), orgasm problem (16.6%), satisfaction problem (21.5%) and pain problems (16.6%). Women at high risk of FSD were significantly associated with age (OR 4.1, 95% CI 1.9 to 9.0), husband's age (OR 4.3 95% C.I 1.9 to 9.3), duration of marriage (OR 3.3, 95% CI 1.6 to 6.8), medical problems (OR 8.5, 95% CI 3.3 to 21.7), menopausal status (OR 6.6, 95% CI 3.1 to 14.3), and frequency of sexual intercourse (OR 10.7, 95% CI 3.6 to 31.7). Multivariate analysis showed that medical problem (adjusted OR 4.6, 95% CI 1.6 to 14.0) and frequency of sexual intercourse (adjusted OR 7.2, 95% CI 2.1 to 24.0) were associated with increased risk of having FSD. Those who practiced contraception were less likely to have FSD. Conclusion. Sexual health problems are prevalent in women attending primary care clinic where one in four women were at high risk of FSD. Thus, primary care physician should be trained and prepared to address this issue. Ishak IH, Low WY, and Othman S. Prevalence, risk factors and predictors of female sexual dysfunction in a primary care setting: A survey finding. J Sex Med 2010;7:3080-3087.